Risky sexual behaviour, alcohol use, self-esteem and exposure to sexual and physical violence among Swedish students who intend to spend a semester abroad: a comparative cross-sectional study - Danehorn, Emil (Linnaeus University, 2020)
Aim: The aim was to investigate risky sexual behavior, alcohol use, self-esteem and exposure to sexual and physical violence among students who intended to spend a semester abroad. We also wanted to investigate whether there were any significant differences between students who intended to spend a semester abroad and students who remain on campus, as well as between male and female students.

Method: comparative cross-sectional design using an online survey containing the NorVold Abuse Questionnaire, Knowledge, attitudes and sexual behaviour in young people in Sweden and Rosenberg´s Self-Esteem Scale. A total of 565 participants took part in the survey, of which 114 were prospective exchange students and 451 were campus students.

Results: The prospective exchange students scored higher on self-esteem (30.9) compared to the campus students (29.0) (p=0.007). The prospective exchange students had engaged in sex under the influence of alcohol over the last six months (70,2%) more than the campus students (53.4%) CI: 16.7(6.7;25.7). Male students were overrepresented in their exposure to physical violence (31.8%) compared to female students (16.5%) CI: 15.3 (7.4;23.7). Female students were overrepresented in their exposure to sexual violence (54,5%) compared to male students (21,9) CI: 33.1(24.5;40.5).

Conclusion: Prospective exchange students have a higher level of self-esteem and engage in risky sexually behaviour more than campus students. There are no prominent differences in exposure to violence between the prospective exchange students and the campus students. However, the overall frequency is high. The most significant differences in exposure to violence are between male and female students. Male students are more frequently exposed to physical violence and female students to sexual violence. However, the prevalence of sexual and physical violence is high for both sexes.

Enkätundersökning riktad till studenter i Kronobergs län och Kalmar län med syfte att undersöka utbytesstudenters sexuella riskbeteende och utsatthet för fysiskt och sexuellt våld innan de åker på utbytesresa jämfört med studenter som stannar kvar på campus. Studien undersöker också om det finns det skillnader mellan de båda grupperna och om det finns det skillnader mellan kön.
Risky sexual behaviour, alcohol use, self-esteem and exposure to sexual and physical violence among Swedish students who intend to spend a semester abroad: a comparative cross-sectional study
Keywords: Violence; Våld; Risky sexual behaviour; Sexuellt riskbeteende; self-esteem; Självkänsla; Students; Studenter; Exchange students; Utbytesstudenter; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin